Construção de vídeo educativo para promoção do autocuidado do idoso com diabetes - Medeiros, Morgana Maria Ramos de (2021)
Introduction: the accelerated growth of the elderly population in Brazil establishes the need for greater attention to the most prevalent diseases in this population. This demographic transition is accompanied by a significant increase in Chronic Noncommunicable Diseases (NCDs). One of the four main NCDs, diabetes mellitus, can cause early death, complications and disability. The management of the disease is still a challenge. Diabetes treatment aims to achieve good glycemic control and needs to be accompanied by continuing education to raise awareness and prepare the individual for self-care. Health education enables the elderly to change lifestyle habits and to overcome problems with diabetes, considering that health behaviors are related to the knowledge acquired. Objectives: conduct an integrative literature review on the importance of health education in the prevention of diabetes complications in the elderly; develop a field study with elderly diabetic patients, users of a teaching hospital, to assess their knowledge of diabetes; to make an educational video to promote self-care and prevent diabetes complications in the elderly. Methodology: this is a methodological study. Initially, an integrative literature review was carried out and then a field research. The research was submitted to the Ethics Committee of the Health Sciences Center and approved under nº 2,190,153, CAAE-67103917.6.0000.5188. The research had the participation of 40 elderly diabetics, of both genders, users of the Endocrinology Outpatient Clinic and hospitalized in the sectors of Medical and Surgical at Hospital Universitário Lauro Wanderley-UFPB. The sample consisted of elderly people who agreed to participate in the research. After data collection, the texts were organized and processed in the IRAMUTEQ software for content analysis and elaboration of the last phase of the research, the making of the educational video. Results: the results of the integrative review showed that appropriate health education enables the elderly to self-manage the disease, promotes self-care and changes in lifestyle through knowledge of nutrition, physical activity, proper use of medications and risk-reducing behavior, considered essential for glycemic control and prevention of complications as a consequence of the disease. The interviewed participants had moderate knowledge about diabetes, difficulty following health professionals' recommendations and little knowledge about screening for diabetic retinopathy and diabetic foot. Final considerations: it is expected that the educational video will achieve its main objective, which is to provide information to the elderly and their families about diabetes, to contribute to health promotion and to prevent complications of diabetes in the elderly. This video can be used comprehensively in health institutions and communities and contributes to stimulate new research related to diabetes and gerontology.